2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00944
|View full text |Cite
|
Sign up to set email alerts
|

Generating Synthetic X-Ray Images of a Person from the Surface Geometry

Abstract: We present a novel framework that learns to predict human anatomy from body surface. Specifically, our approach generates a synthetic X-ray image of a person only from the person's surface geometry. Furthermore, the synthetic Xray image is parametrized and can be manipulated by adjusting a set of body markers which are also generated during the X-ray image prediction. With the proposed framework, multiple synthetic X-ray images can easily be generated by varying surface geometry. By perturbing the parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Image synthesis methodologies have also been proposed in the context of chest X-rays (Teixeira et al 2018). Our work is significantly different in the sense that we are specifically interested in synthesizing a particular class, whereas in Teixeira et al (2018) X-rays are generated from surface geometry for landmark detection tasks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Image synthesis methodologies have also been proposed in the context of chest X-rays (Teixeira et al 2018). Our work is significantly different in the sense that we are specifically interested in synthesizing a particular class, whereas in Teixeira et al (2018) X-rays are generated from surface geometry for landmark detection tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Image synthesis methodologies have also been proposed in the context of chest X-rays (Teixeira et al 2018). Our work is significantly different in the sense that we are specifically interested in synthesizing a particular class, whereas in Teixeira et al (2018) X-rays are generated from surface geometry for landmark detection tasks. While some generative methods only require paired data in the source domain with target domain consisting of unlabeled examples, Cohen et al (2018) have demonstrated that the phenomenon of hallucinating features (e.g., adding or removing tumors leading to a semantic change) leads to a high bias in these domain adaptation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research in deep learning has shown encouraging progress in detecting 3D landmarks from surface data ( Papazov et al, 2015 ; He et al, 2019 ; Liu et al, 2019 ). Teixeira et al (2018 ) introduced a method to estimate 2D positions of internal body landmarks from a 2.5D surface image of the torso generated by orthographically projecting the 3D skin surface. Such methods, however, do not generalize to 3D data, since it would require representing landmark likelihood as a Gaussian distribution over a dense 3D lattice, and the memory required for representing 60 such lattices, one for each landmark, would be overwhelming.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of X-Ray Dose in Chest Tomosynthesis was investigated by Miroshnychenko [18]. Generating a Synthetic X-Ray Image of a Person from Surface Geometry was investigated by Teixeira [19]. Classification of modalities and detection of concepts on medical images using distance transfer learning was investigated by Singh [20].…”
Section: Comparison Of Image Enhancement Methods For Lumbarmentioning
confidence: 99%